Increased 25(OH)D3 level in redheaded people: Could redheadedness be an adaptation to temperate climate? - Flegr, Jaroslav; Sýkorová, Kateřina; Fiala, Vojtěch; Hlaváčová, Jana; Bičíková, Marie; Máčová, Ludmila; Kaňková, Šárka (Experimental dermatology, 2020)
About 1-2% of European population are redheaded, meaning they synthesize more pheomelanin than eumelanin, the main melanin pigment in humans. Several mutations could be responsible for this phenotype. It has been suggested that corresponding mutations spread in Europe due to a founder effect shaped either by a relaxation of selection for dark, UV-protective phenotypes or by sexual selection in favour of rare phenotypes. In our study, we investigated the levels of vitamin D precursor 25(OH)D3 (calcidiol) and folic acid in the blood serum of 73 redheaded and 130 non-redheaded individuals. In redheaded individuals, we found higher 25(OH)D3 concentrations and approximately the same folic acid concentrations as in non-redheaded subjects. 25(OH)D3 concentrations correlated with the intensity of hair redness measured by two spectrophotometric methods and estimated by participants themselves and by independent observers. In non-redheaded individuals, 25(OH)D3 levels covaried with the amount of sun exposure and intensity of suntan while in redheaded individuals, this was not the case. It suggests that increased 25(OH)D3 levels in redheaded individuals are due to differences in physiology rather than in behaviour. We also found that folic acid levels increased with age and the intensity of baldness and decreased with the frequency of visiting tanning salons. Our results suggest that the redheaded phenotype could be an evolutionary adaptation for sufficient photosynthesis of provitamin D in conditions of low intensity of UVB radiation in central and northern parts of Europe.
Keywords: molekulární evoluce; cancer; UVB; Aging; pigmentace kůže; Hair Color; opálení pleti; Male; Folic Acid; fyziologická adaptace; Skin Pigmentation; Middle Aged; alopecie; mužské pohlaví; Calcifediol; studie případů a kontrol; sluneční záření; Adult; barva vlasů; kyselina listová; pigmentation; Climate; stárnutí; human evolution; ženské pohlaví; Humans; vitamin D; Sunlight; baldness; lidé středního věku; podnebí; Suntan; Alopecia; dospělí; kalcifediol; Female; lidé; Case-Control Studies; Adaptation, Physiological; Evolution, Molecular